Konsep dan Manajemen Zakat Dalam Perspektif Hukum Positif di Indonesia: Tinjauan Hukum Islam (Prinsip Maqasid al Syariah) - Aries Musnandar; Sutomo (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2022)
The legal system in Indonesia has its characteristics. The influence of Dutch law in the legal system in Indonesia is quite dominant. Customary law and Islamic law are also accommodated in Indonesian national law. Another thing that comes from fiqh muamalah (Islamic jurisprudence of economics) and gets government attention is related to the conceptual issue of zakat and its management in particular. This research uses qualitative with the descriptive method of analysis. Moreover, to sharpen the analysis results the authors also accommodate the discussions and unstructured interview results with the concerned parties such as colleague researchers, and experts about the theme raised by the author. The results of the study indicate that the optimal implementation of zakat will be able to bridge the gap between rich and poor. As with taxes, zakat is also a part of state revenue, therefore the linkage between tax and zakat is very close.